The Influence of the Flipped Classroom Learning Model on English Literature Students’ in Poetry Course at Pakuan University - Kristyowati, Dyah; Kurniasari, Resty Widya; Suharyati, Henny; Jayawinangun, Roni (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
ABSTRACT This study aims to investigate the application of the flipped classroom learning model to influence class-A students' assesment in the English Literature Study Program at Pakuan University, Bogor. This type of research employs classroom action research with 50 students in class A and B  during the odd semester of 2022/23 enrolled in Poetry class . The collection of data was conducted with the use of speaking tests and observation sheets. Analyzing the data, an average score of 80% of students who had problems with speaking because they did not reach the passing standard value established in the lecture contract, and only 17% of students who were able to achieve the passing grade standard were obtained in the pre-action phase. The cycle I graduation rate increased to 46%, and in cycle II, 100% of students achieved the standard passing score. The results of this study indicate that the flipped classroom learning model can influence students' assessment .Keywords: Poetry Analysis; Flipped Classroom Learning Model, Assesment